Population Pharmacokinetics and Exposure‐Response Relationship of Luspatercept, an Erythroid Maturation Agent, in Anemic Patients With β‐Thalassemia. (21st July 2020) - Chen, Nianhang; Kassir, Nastya; Laadem, Abderrahmane; Giuseppi, Ana Carolina; Shetty, Jeevan; Maxwell, Stephen E.; Sriraman, Priya; Ritland, Steve; Linde, Peter G.; Budda, Balasubrahmanyam; Reynolds, Joseph G.; Zhou, Simon; et al.
Abstract: β‐Thalassemia is an inherited blood disorder resulting from defects in hemoglobin production, leading to premature death of red blood cells (RBCs) or their precursors. Patients with transfusion‐dependent β‐thalassemia often need lifelong regular RBC transfusions to maintain adequate hemoglobin levels. Frequent transfusions may lead to iron overload and organ damage. Thus, there is a large unmet need for alternative therapies. Luspatercept, a first‐in‐class erythroid maturation agent, is the first approved therapy in the United States for the treatment of anemia in adult patients with β‐thalassemia who require regular RBC transfusions. The population pharmacokinetics and exposure‐response relationship of luspatercept were evaluated in 285 patients with β‐thalassemia. Luspatercept displayed linear and time‐invariant pharmacokinetics when administered subcutaneously once every 3 weeks. Body weight was the only clinically relevant covariate of luspatercept clearance, favoring weight‐based dosing. Magnitude and frequency of hemoglobin increase, if not influenced by RBC transfusions, was positively correlated with luspatercept area under the serum concentration‐time curve (AUC), 0.2‐1.25 mg/kg, whereas a significant reduction in RBC units transfused was observed in frequently transfused patients. The probability of achieving ≥33% or ≥50% reduction in RBC transfusion burden was similar across the time‐averaged AUC (0.6‐1.25 mg/kg), with the 1 mg/kg starting dose sufficient for most early responders (71%‐80%). Increasing luspatercept AUC (0.2‐1.25 mg/kg) did not increase incidence or severity of treatment‐emergent adverse events. These results provide a positive benefit‐risk profile for the recommended luspatercept doses (1‐1.25 mg/kg) in treating adult patients with β‐thalassemia who require regular RBC transfusions.